Vegetation incorporation effects on the roofs in urban area in the continental tropical climate - Rosseti, Karyna de Andrade Carvalho (2015)
In most urban areas there are a few residual spaces left to be converted into green areas. A possible solution for the incorporation of vegetation in the urban area would be turning the existing roofs into green ones. The purpose of this research is to assess whether the incorporation of green roofs into existing building roofs in low-density urban areas could alter the termo-hygrometric conditions to the pedestrian level. The methodology consists on the performing of computer simulations in urban area scenarios, located in a tropical climate city (Cuiabá-MT), by adding vegetation of 10%, 50% and 100% to the existing roofs in the research area. It is shown the existence of interference association between the occupation density of the roofs by vegetation and the cooling and humidification phenomenon of the air, to the pedestrian level, in low-density condition urban areas. The most expressive effects caused by a green roof in temperature and absolute humidity are contained in the yard area in the lee of the houses that added vegetation to the roofs.